2017
DOI: 10.1002/2327-6924.12524
|View full text |Cite
|
Sign up to set email alerts
|

Health maintenance practices and healthcare experiences among international university students

Abstract: Background and purpose While over a million international students attend U.S. universities, there is little information to guide providers on their care. Differences in language and health beliefs can lead to misunderstandings and poor outcomes. The purpose of this study was to describe the health practices and healthcare experiences of international students before and after they move to the United States to carve out specific quality improvement activities at a student health center. Methods International s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…There was a varied understanding of insurance coverage, supporting results found in the United States. 19,20 Nonetheless, no participants reported that cost might dissuade them from accessing appropriate health care. However, it is important to recognise the exception of HIV PrEP, which is not publicly funded for international students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a varied understanding of insurance coverage, supporting results found in the United States. 19,20 Nonetheless, no participants reported that cost might dissuade them from accessing appropriate health care. However, it is important to recognise the exception of HIV PrEP, which is not publicly funded for international students.…”
Section: Discussionmentioning
confidence: 99%
“…The compulsory Australian Overseas Student Health Cover may complicate the issue, with complex terms and conditions varying among insurance companies. Two American studies have found that international students lack knowledge regarding insurance coverage, 19,20 although there are no Australian data. Nevertheless, it is likely that complex insurance creates challenges for students accessing health care.…”
Section: Introductionmentioning
confidence: 99%